A comparison of student attitudes towards languages other than English (LOTEs) in Turkey and in the USA - Nur Akkuş Çakır; Nihan Aylin Ünlü (Informascope, 2019)
The study aimed at investigating learners' attitudes towards languages other than English (LOTEs). The study also explored participant instructors' views on students' attitudes towards LOTEs. In order to collect data, a language attitude questionnaire was designed by adapting Students' Attitude Toward Foreign Language (SAFL) instrument. The study sampled a total of 316 students, 261 from Turkey, 55 from the USA. University students enrolled in a second language course in the USA and Turkey were compared in terms of their responses to SAFL items as well as their attitude scores for each of the 4 dimensions. Separate confirmatory factor analyses were conducted for each sample with 4 varimax rotated, orthogonal factors. Factor scores for each individual were computed based on the weights identified by the factor analysis to obtain general measures of motivation, students' effort and instructor's role, self-confidence and self-interest, and students' anxiety. According to the research findings students learning LOTEs have favorable attitudes towards the language they are learning both in Turkey and the USA due to their interests in the cultural products of the countries speaking those languages and increasing educational opportunities.